Original paperTRAINING LOAD, IMMUNE SYSTEM, UPPER RESPIRATORY SYMPTOMS AND PERFORMANCE IN WELL-TRAINED CYCLISTS THROUGHOUT A COMPETITIVE SEASON - Ferrari, H.G.; Gobatto, C.A.; Manchado-Gobatto, F.B. (Biology of Sport, 2013)
This study aimed to evaluate the leukocyte subset counts, serum immunoglobulin A, performance and upper respiratory symptoms (URS), as well as their interrelationships, of well-trained cyclists for a 29-week training season using monitored loads. The season was divided into three phases: preparatory (nine weeks), first competitive phase (nine weeks) and second competitive phase (11 weeks). The sample consisted of eight well-trained cyclists, aged 18 ± 2 years. Immunological parameters and performance were evaluated during weeks 1 (baseline), 10 (early first competitive phase), 19 (early second competitive phase) and 29 (end of the second competitive phase). The training loads (volume x rating of perceived exertion) were monitored daily while the monitoring of URS was performed every 15 days using the WURSS-44 questionnaire. The data were analyzed using a one-way ANOVA and a Pearson correlation test with the significance level set at p ≤ 0.05. No significant differences were found for training load, leukocyte subset counts or serum immunoglobulin A among the three phases. However, serum immunoglobulin A was 50.9% below the control group values. URS were significantly higher during the preparatory period, and there were significant correlations between URS and training load (strain) in the preparatory period (r = 0.72, p = 0.032) and second competitive phase (r = 0.73, p = 0.036). In conclusion, indicators of training load without a significant change throughout the season did not significantly affect immune parameters measured; however, the increase of strain can cause an increase of upper respiratory symptoms throughout the season, but without loss of performance.